2010
DOI: 10.5138/ijdd.2010.0975.0215.02046
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric method development and validation of itopride hydrochloride in bulk and dosage form.

Abstract: A simple, precise and economical spectrophotometric method for the estimation of Itopride hydrochloride in pharmaceutical bulk and tablet dosage form was developed and validated. Identification was carried out using a UVvisible double beam spectrophotometer detector with working wavelength at 258nm in 0.1N HCl medium. The method was validated with respect to its specificity, linearity range, accuracy, and precision in analytical media. Itopride hydrochloride show the maximum absorbance (λmax) at 258 nm, Regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Quite a lot of analytical methods were reported for the determination of Itopride hydrochloride in its pure form, pharmaceutical preparations and human plasma, including spectrophotometric methods [3][4][5], electrochemical method [6], TLC [7], liquid chromatography with ultraviolet detection [8][9][10][11][12], chemiluminescence detection [13] and fluorescence detection [14][15][16]. On the other hand, RB was analyzed by applying several methods like; spectrophotometric methods [17][18][19][20][21][22], chemometric method [23] and spectroflourimetric methods [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Quite a lot of analytical methods were reported for the determination of Itopride hydrochloride in its pure form, pharmaceutical preparations and human plasma, including spectrophotometric methods [3][4][5], electrochemical method [6], TLC [7], liquid chromatography with ultraviolet detection [8][9][10][11][12], chemiluminescence detection [13] and fluorescence detection [14][15][16]. On the other hand, RB was analyzed by applying several methods like; spectrophotometric methods [17][18][19][20][21][22], chemometric method [23] and spectroflourimetric methods [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical methods have been developed for the determination of PAN in pharmaceutical preparations such as spectrophotometric methods [3][4][5][6], HPLC methods [7][8][9][10], HPTLC-densitometric methods [11,12] and liquid chromatographic-tandem mass methods (LC-MS/MS) [13,14]. Also several methods have been reported for the determination of ITH in pharmaceutical preparations such as spectrophotometric methods [15][16][17], HPLC methods [18][19][20], HPTLC-densitometric methods [21,22] and spectroflourimetric methods [23]. Simultaneous determination of PAN and ITH has been achieved by different spectrophotometric methods [24][25][26], HPLC methods [27,28], HPTLCdensitometric methods [29], spectroflourimetric methods [23].…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey revealed that ITP has been determined by spectrophotometry , spectrofluorimetry , high‐performance thin‐layer chromatography (HPTLC) and several HPLC methods using UV , fluorescence , chemiluminescence and MS detection . Several methods have been reported for the determination of DOM including potentiometry , anodic differential pulse voltammetry , HPLC‐MS and HPLC with fluorescence detection .…”
Section: Introductionmentioning
confidence: 99%